Collective action problems and the role of South African business in national and regional accords - Nicoli Nattrass (South African Journal of Business Management, 1997)
This article examines some of the collective action problems which beset South African business in national and regional accords. The first part concludes that incomes policy type accords at national level are unlikely to be successful in South Africa. The main part of the article considers accords at subnational level where conflicts of interest are more easily (but not entirely) resolved. This is done by means of two case studies of business acting collectively to promote regional or local development. The first looks at the role of organized business in the Eastern Cape Socio-Economic Consultative Council (ECSECC). It is suggested that the geographical divide between the various business organizations undermines the potential for collective action. The second describes the more successful local housing accord which was negotiated in Port Elizabeth.
Keywords: 650